2016
DOI: 10.1021/jacs.6b03563
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Specific Electrical Purification of Nucleic Acids with Nanoporous Gold Electrodes

Abstract: Nucleic acid-based biosensors have enabled rapid and sensitive detection of pathogenic targets; however, these devices often require purified nucleic acids for analysis since the constituents of complex biological fluids adversely affect sensor performance. This purification step is typically performed outside the device, thereby increasing sample-to-answer time and introducing contaminants. We report a novel approach using a multifunctional matrix, nanoporous gold (npAu), which enables both detection of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…8 Enzymes such as laccase have also been covalently linked to SAMs formed from lipoic acid activated to produce reactive esters that form an amide linkage to a lysine residue on the enzyme. 9 Thiolated single-stranded DNA oligonucleotides have been directly assembled onto NPG, 10 as have thiolated aptamers. 11 In the case of DNA and aptamer immobilization, subsequent exposure to a short chain alkanethiol such as mercaptohexanol has been applied to cover exposed sites, limit nonspecific adsorption, and promote better orientation of the DNA strand.…”
Section: Probe Immobilization and Target Molecule Capturementioning
confidence: 99%
See 1 more Smart Citation
“…8 Enzymes such as laccase have also been covalently linked to SAMs formed from lipoic acid activated to produce reactive esters that form an amide linkage to a lysine residue on the enzyme. 9 Thiolated single-stranded DNA oligonucleotides have been directly assembled onto NPG, 10 as have thiolated aptamers. 11 In the case of DNA and aptamer immobilization, subsequent exposure to a short chain alkanethiol such as mercaptohexanol has been applied to cover exposed sites, limit nonspecific adsorption, and promote better orientation of the DNA strand.…”
Section: Probe Immobilization and Target Molecule Capturementioning
confidence: 99%
“…Several groups have reported that NPG films are highly biofouling-resilient and are able to sustain electrochemical function in protein solutions. 10,17 This has been attributed to NPG morphology at a certain pore size (tens of nanometers), which blocks the permeation of large proteins while still allowing the transport of small ions and reporter molecules, effectively serving as a biofouling-resilient electrode (Figure 1b and Figure 2c).…”
Section: Probe Immobilization and Target Molecule Capturementioning
confidence: 99%
“…Np-Au is produced by dissolving silver from a silver-rich gold alloy in heated nitric acid, where gold atoms go under surface diffusion to create a bicontinuous open-pore structure. [14] A wide range of attractive features, including high surface area-tovolume ratio, [15] tunable morphology [16] and surface chemistry, [17] biocompatibility, [18] electrical conductivity, [16a] and compatibility with conventional microfabrication techniques, [19] have led to interest from the sensing and catalysis community. These features, also desirable for precise control of molecular release, enable high small-molecule loading capacity and release kinetics, paved the way for np-Au's use in molecular release applications.…”
Section: Introductionmentioning
confidence: 99%
“…Properties of the drug molecules (e.g., electrical charge, size, chemical reactivity), the materials (e.g., morphology, surface charge), and the liquid medium where the molecules are delivered (e.g., ionic strength, pH) are all crucial factors in dictating drug delivery performance 2,6 . Nanoporous gold (np-Au), with its high effective surface area, well established gold-thiol-mediated surface modifications, and tunable pore morphology, is a promising material for drug delivery applications and studying the influence of physicochemical surface properties on the moleculeloading capacity and release kinetics [8][9][10][11][12][13][14][15] . Our previous studies have focused on the effect of pore morphology and elution medium constituents on the molecular release from np-Au coatings 11,16 .…”
Section: Introductionmentioning
confidence: 99%